COMMUNICATIVENESS OF THE ASSONANCE STYLISTIC DEVICE IN ENGLISH AND UZBEK LITERATURE TEXTS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This study examines the communicative role of assonance in English and Uzbek literary texts. Assonance, as the repetition of vowel sounds, enhances emotional expression, rhythm, and aesthetic effect in literature. Using comparative stylistic analysis, the research shows that English literature employs assonance mainly for subtle emotional and psychological nuance, while Uzbek literature uses it as a core expressive device influenced by oral tradition and vowel harmony. The findings confirm that assonance is a universal stylistic means that strengthens meaning, emotional impact, and communicative effectiveness across both languages.